Anti-Tn Monoclonal Antibody Attenuates Hyperoxia-Induced Lung Injury by Inhibiting Oxidative Stress and Inflammation in Neonatal Mice - Chen, Chung-Ming; Hwang, Jaulang; Chou, Hsiu-Chu; Chen, Chinde (Frontiers in Pharmacology, 2020)
Maternal immunization with Tn vaccine increases serum anti-Tn antibody titers and attenuates hyperoxia-induced lung injury in neonatal rats. This study determined whether anti-Tn monoclonal antibody can protect against hyperoxia-induced lung injury in neonatal mice. Newborn Balb/c mice were exposed to room air (RA) or normobaric hyperoxia (85% O2) for 1 week, creating four study groups as follows: RA + phosphate-buffered saline (PBS), O2 + PBS, RA + anti-Tn monoclonal antibody, and O2 + PBS. The anti-Tn monoclonal antibody at 25 μg/g body weight in 50 μL PBS was intraperitoneally injected on postnatal days 2, 4, and 6. Hyperoxia reduced body weight and survival rate, increased mean linear intercept (MLI) and lung tumor necrosis factor-α, and decreased vascular endothelial growth factor (VEGF) expression and vascular density on postnatal day 7. Anti-Tn monoclonal antibody increased neonatal serum anti-Tn antibody titers, reduced MLI and cytokine, and increased VEGF expression and vascular density to normoxic levels. The attenuation of lung injury was accompanied by a reduction in lung oxidative stress and nuclear factor-κB activity. Anti-Tn monoclonal antibody improves alveolarization and angiogenesis in hyperoxia-injured newborn mice lungs through the suppression of oxidative stress and inflammation.